Effectiveness of blended active learning framework using Bring Your Own Device Learning (BYODL), Project Based Learning (PPBL) and Gamification Learning (GL) - Azana Hafizah Mohd Aman,; Rosilah Hassan,; Wahiza Wahi,; Hasimi Sallehuddin,; Abdul Hadi Azman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Active learning commonly entails learning techniques that engage students in the learning process. Two important elements of active learning are student activity and student engagement. The objective of this paper is to establish the effectiveness of an Active Learning framework based on multiple approaches to increase student engagement. This research utilizes three techniques that were blended together to optimize the effect of the three important elements of active learning, which are Bring Your Own Device Learning (BYODL), Project Based Learning (PPBL) and Gamification Learning (GL). At the start of the PPBL active learning process, students were grouped in five to six team members and each group wasgiven a specific project to be submitted towards the end of the semester. All assignments were uploaded in the I-Folio system for easy references. For the purpose of continuous BYODL and GL learning, students were given online attendance with QR code scan and questions from previous lessons via Google form at the beginning of each lesson to promote active learning. During the lesson, students were given short quizzes via Kahoot application and PBL question with snapshot answers via Google form and I-Folio assignment system. The results show that these techniques were found to be effective in increasing students’ engagement and involvement in active learning. In conclusion, the framework that blends three approaches together has effectively optimized active learning with more than 90% students’ engagement rate and have proven to be constructive to boost students’ engagement and involvement in active learning.